AI in Teaching English to IT Specialists. - Tsyntar, Natalia (Прикарпатський національний університет імені Василя Стефаника, 2025)
Artificial Intelligence (AI) has been revolutionizing various fields of modern life, including education. Among its many applications, AI plays a crucial role in language learning, particularly in teaching English to IT specialists. As technology continues to advance, professionals in the IT sector must possess strong English language skills to be able to collaborate internationally, access technical resources, and engage with global trends. AI-powered tools offer innovative solutions that enhance the efficiency and effectiveness of English learning for IT specialists.